'To be able to support her, I must feel calm and safe': pregnant women's partners perceptions of professional support during pregnancy - Caroline Bäckström; Stina Thorstensson; Lena B. Mårtensson; Rebecca Grimming; Yrsa Nyblin; Marie Golsäter (BMC, 2017)
Abstract Background Professional support does not always meet the needs of expectant fathers or co-mothers. The way in which professional support is offered during pregnancy varies internationally, depending on the country. In order to attain a greater understanding of partners' experiences of professional support, it is necessary to further illuminate their perceptions of it. The aim of this study was therefore to explore pregnant women's partners' perceptions of professional support during pregnancy. Methods Qualitative research design. Partners of pregnant women were interviewed during gestational week 36-38. Individual semi-structured interviews were used to explore the partners' perceptions. The data was analysed using a phenomenographic approach. The study was performed in a county in south-western Sweden; the data collection was conducted from November 2014 to February 2015. Fourteen partners (expectant fathers and co-mothers) of women who were expectant first-time mothers with singleton pregnancies, were interviewed. Results The findings of the study are presented through four descriptive categories: Ability to absorb adequate information; Possibility to meet and share with other expectant parents; Confirmation of the partner's importance; and Influence on the couple relationship. Using a theoretical assumption of the relationship between the categories showed that the fourth category was influenced by the other three categories. Conclusions The partners perceived that professional support during pregnancy could influence the couple relationship. The partners' ability to communicate and to experience togetherness with the women increased when the expectant couple received professional support together. The support created also possibilities to meet and share experiences with other expectant parents. In contrast, a lack of support was found to contribute to partners' feelings of unimportance. It was essential that the midwives included the partners by confirming that they were individuals who had different needs for various types of professional support. The partners perceived it easier to absorb information when it was adequate and given with a pedagogic that made the partners become interested and emotionally engaged.